2021
DOI: 10.3389/fcimb.2021.609722
|View full text |Cite
|
Sign up to set email alerts
|

Probiotic Gastrointestinal Transit and Colonization After Oral Administration: A Long Journey

Abstract: Orally administered probiotics encounter various challenges on their journey through the mouth, stomach, intestine and colon. The health benefits of probiotics are diminished mainly due to the substantial reduction of viable probiotic bacteria under the harsh conditions in the gastrointestinal tract and the colonization resistance caused by commensal bacteria. In this review, we illustrate the factors affecting probiotic viability and their mucoadhesive properties through their journey in the gastrointestinal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
92
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 216 publications
(127 citation statements)
references
References 144 publications
(185 reference statements)
1
92
0
Order By: Relevance
“…This is also the case of whole cells, including lactic acid bacteria (LAB), Bifidobacteria, Escherichia coli Nissle 1917, and beneficial molecules such as bivalent fusion protein r-BL with recombinant protein U-Omp19, Garcinia mangostana L. ethanolic extract, and insulin [5][6][7][8][9][10][11]. As these bioactive Biomolecules 2021, 11, 922 2 of 19 molecules reach the small intestine lumen, they need to come across an extracellular mucus layer to finally reach the surface of the brush border for absorption [12]. Such a physiological barrier poses a significant obstacle for absorption of administered compounds since the thickness varies from 30 to 300 µm, increasing from the intestine to the rectum [12].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…This is also the case of whole cells, including lactic acid bacteria (LAB), Bifidobacteria, Escherichia coli Nissle 1917, and beneficial molecules such as bivalent fusion protein r-BL with recombinant protein U-Omp19, Garcinia mangostana L. ethanolic extract, and insulin [5][6][7][8][9][10][11]. As these bioactive Biomolecules 2021, 11, 922 2 of 19 molecules reach the small intestine lumen, they need to come across an extracellular mucus layer to finally reach the surface of the brush border for absorption [12]. Such a physiological barrier poses a significant obstacle for absorption of administered compounds since the thickness varies from 30 to 300 µm, increasing from the intestine to the rectum [12].…”
Section: Introductionmentioning
confidence: 99%
“…As these bioactive Biomolecules 2021, 11, 922 2 of 19 molecules reach the small intestine lumen, they need to come across an extracellular mucus layer to finally reach the surface of the brush border for absorption [12]. Such a physiological barrier poses a significant obstacle for absorption of administered compounds since the thickness varies from 30 to 300 µm, increasing from the intestine to the rectum [12]. Consequently, only a tiny fraction (tight junction proteins allow the exchange of molecules with molecular weight < 500 Da [13]) made it to the systemic circulation.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…strain Ab1 can successfully colonize the digestive tract of different fish species, and P. acidilactici can remain in the intestine for at least 17 days without continual dietary administration [ 11 ]. However, some studies have also shown that probiotics ingested by humans are excreted in large quantities shortly after drug administration [ 12 ]. Similarly, Grimm et al indicated that Bifidobacteria could not colonize the intestine of specific pathogen-free mice, but were able to colonize the intestine of germ-free mice [ 13 ].…”
Section: Introductionmentioning
confidence: 99%